Convergent evidence for mGluR5 in synaptic and neuroinflammatory pathways implicated in ASD. (May 2015) - Zantomio, Daniela; Chana, Gursharan; Laskaris, Liliana; Testa, Renee; Everall, Ian; Pantelis, Christos; Skafidas, Efstratios
Highlights: Review of two important aetiological pathways in Autism. The role of mGluR5 in Autism and neuroinflammation in relation to the synapse. A focused review combining data from different experimental modalities. Unifying thinking on mGluR5 and the role of microglia in Autism. Abstract: The pathogenesis of Autism Spectrum Disorder (ASD), a serious neurodevelopmental disorder, is poorly understood. We review evidence for alterations in glutamatergic signalling in the aetiology of ASD, with a focus on the metabotropic glutamate receptor-5 (mGluR5). mGluR5 signalling is important for synapse formation, neuroplasticity and long term potentiation as well as neuroprotection and has been shown to have a regulatory role in neuroinflammation. Evidence for neuroinflammation in ASD is supported by increase in pro-inflammatory cytokines in the blood and cerebrospinal fluid (CSF) and increased number and activation of microglia in postmortem dorsolateral prefrontal cortex (DLPFC). mGlur5 signalling has also been shown to downregulate microglial activation. Therefore, we focus on mGluR5 as a potential unifying explanation for synapse alteration and neuroinflammation seen in ASD. Data from mGluR5 knockout mouse models, and syndromic and non syndromic forms of ASD are discussed in relation to how alterations in mGluR5 are associated with ASD symptoms. This review supports altered mGluR5 functioning as a convergent point in ASD pathogenesis and indicates more research is warranted into mGluR5 as a potential therapeutic target.